Temporal Fuzzy Case-based Reasoning Retrieval - Tawin Tanawong (Science Faculty of Chiang Mai University, 2019)
When we try to find the old case by matching problem description attribution to solve the new problem, we find an important obstacle which is the attribution ambiguity of problem description, especially, when attribute value changes the time, it changes the meaning of attribute. Therefore, it causes terrible new problem solving out of the old case solution. This study proposes new problem solution which is ambiguous in terms of 3 types of time problems: current time, sequence time and non-sequence time respectively. Finding case by the principle of ontology and TFSQL programming from cases in front of temporal fuzzy case. In addition, we set temporal fuzzy linguistic term to explain ambiguous problem under changed time including saving the set of commands for managing fuzzy expression under Meta Knowledge Base. We saved the case in oracle relational database management system which is designed for a range of case factors in the form of conceptual meta scheme by Natural Language Information Analysis Method (NIAM). Mapping cases as relational scheme for collecting the details of cases.